Tips & techniques to improve your total image grooming, dressing and body language : your success starts here! - Furris, Nick; Hackney, Gary; Linx Educational Publishing (Atlantic Beach, Fla. : Linx Educational Pub., 2004)
Provides basic grooming techniques, introduces clothing styles appropriate for the workplace, and concludes with examples of how we communicate with body language
Title from title screen
Executive producer, Lina Ingraham ; associate producer/writer, Katherine K. Yonge ; director of photography, Pat Herbert ; editor, Chris Bearers
Keywords: Beauty, Personal; Health and hygiene; Body language; Clothing and dress